Tsc1-mTORC1 signaling controls striatal dopamine release and cognitive flexibility - Polina Kosillo (Nature Portfolio, 2019)
Tuberous Sclerosis Complex (TSC) is a neurodevelopmental disorder caused by mutations in the TSC1 or TSC2 genes, which negatively regulate mTORC1 signalling. Here the authors selectively delete Tsc1 from dopamine neurons in mice and find impairments in striatal dopamine release that are sufficient to reduce cognitive flexibility.